SUSTAINABLE MATERIALS NATURAL COLORS THE SUNGGING WAYANG PROCESS AS A REBRANDING OF THE GENDENG BANGUNJIWO WAYANG ARTISAN COMMUNITY IN BANTUL, YOGYAKARTA - Susanto, Moh. Rusnoto; Mariah, Siti; Lukitaningsih, Ambar; Surono, Sugiyarto; Kinanti, Marlita Diyah Wening; Idam, Gabriela; Azis, Septiyan Ibnu; Prasetyo, Haryanto Nur; Damayanti, Fanita; Maulida, Tasya (Yayasan Education and Social Center, 2025)
This community service project aims to develop natural dyes (sustainability materials) to support the wayang puppet painting process as a rebranding strategy for the artisan community in Gendeng Hamlet, Bangunjiwo, Bantul, Yogyakarta. The implementation method involves a series of activities carried out through a Participatory Action Research (PAR) approach, involving artisans, academics, and facilitators. The stages include training, mentoring, exploration of local materials (such as Indigofera leaves, tingi bark, and turmeric), and applied trials on wayang puppets. The results of the activities showed an increase in the artisans' capacity in natural dye extraction and application techniques, more aesthetically pleasing and environmentally friendly visual quality of wayang, and the formation of a new community identity with the branding “Wayang Warna Alam” (Natural Color Wayang). This innovation not only increases the added value of wayang products but also strengthens cultural and ecological sustainability and opens up market opportunities in the context of the creative economy.